2012
DOI: 10.1016/j.acvd.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and subsequent blood pressure: A meta-analysis

Abstract: Hypertension is becoming an important health problem in many countries. The 'small baby syndrome hypothesis' suggests that an inverse linear relationship exists between birth weight and later risk of hypertension; however, this relationship is under debate. We conducted a meta-analysis to examine the association between birth weight and subsequent blood pressure. Among 78 studies reporting on the association between birth weight and subsequent blood pressure, 20 articles (reporting 27 original studies) were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(161 citation statements)
references
References 45 publications
9
145
5
2
Order By: Relevance
“…LBW and prematurity have consistently been associated with increased risk of higher blood pressure in later life (Table 3) 54,55 . A recent metaanalysis of 27 studies reported a 2.28 mmHg (95% CI, 1.24-3.33 mmHg) increase in systolic blood pressure in subjects who had a birth weight below compared to above 2.5 Kg 55 . Unfortunately most studies to date have not distinguished between LBW as a result of growth restriction at any gestational age, or prematurity with AGA.…”
Section: Birth Weight Prematurity and Blood Pressurementioning
confidence: 99%
“…LBW and prematurity have consistently been associated with increased risk of higher blood pressure in later life (Table 3) 54,55 . A recent metaanalysis of 27 studies reported a 2.28 mmHg (95% CI, 1.24-3.33 mmHg) increase in systolic blood pressure in subjects who had a birth weight below compared to above 2.5 Kg 55 . Unfortunately most studies to date have not distinguished between LBW as a result of growth restriction at any gestational age, or prematurity with AGA.…”
Section: Birth Weight Prematurity and Blood Pressurementioning
confidence: 99%
“…The literature includes studies on small babies (below 2,500 g at birth), small for gestational age (SGA) babies (birth weight is related to gestational week, sex, and local birth weight references), and fetal growth-restricted babies (in which a previously harmonic growth is impaired by a relevant pathologic event). These definitions partly overlap, but only SGA and growth-restricted babies have a definite pathologic meaning (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover several evidences have been accrued in the past, unanimously highlighting that a small BW, as observed in preterm births, is associated with the development of arterial hypertension later, even in children or in adolescents. 1,20 The reason of this inverse relation between small BW and increased BP has yet not been fully clarified, suggesting that a growth retardation in utero may lead to a significantly greater risk for the development of the cluster of metabolic syndrome's correlates (diabetes, hypertension, dyslipidemia, obesity) and, consequently, to the risk of any among the associated cardiovascular events, later in the adult life.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Among correlates of metabolic syndrome obesity seems, however, to be an exception since the majority of studies has pointed out that there is a direct, instead of an inverse, relationship between BW and obesity in children, adolescents or even in adults. 9 The consequence of this, in the light of the strict link existing between obesity and arterial hypertension, is that in obese subjects an attenuated or even a reversed relation between a small BW and raised blood pressure (BP) in adult life may be expected.…”
Section: Introductionmentioning
confidence: 99%